Antibacterial effect of Moringa oleifera on Staphylococcus aureus and Pseudomonas aeruginosa isolated from raw milk and some dairy products with special reference to biofilm gene expression - Rowyda M.Y. Elshazely; Ibrahim H. Amer; Salah F.A. Abd-El Aal; Asmaa B.M.B. Tahoun (Open Veterinary Journal, 2024)
Background: Pseudomonas aeruginosa (P. aeruginosa) and Staphylococcus aureus (S. aureus) are well defined as food poisoning pathogens which are highly resistant and need continuous studies. Aim: The purpose of the work was to examine phenotypic and genotypic characters of both P. aeruginosa and S. aureus, and treatment trial with medicinal plant. Methods: Samples were examined for isolation of P. aeruginosa and S. aureus on selective media followed by biochemical confirmation, biofilm formation, genes detection, and expression of P. aeruginosa pslA biofilm gene was performed by qRT-PCR after treatment with 0.312mg/ml Moringa oleifera aqueous extract as a MIC. Results: The highest isolation rate of P. aeruginosa was 20% from both raw milk and kariesh cheese, followed by 16% and 12% from ice cream and processed cheese, respectively, while the highest isolation rate of S. aureus 36% from raw milk followed by 28% in ice cream and 16% in both kariesh cheese and processed cheese. 30% of P. aeruginosa isolates were biofilm producers, while only 21% of S. aureus isolates were able to produce biofilm. The P. aeruginosa isolates harbor virulence-associated genes nan1, exoS, toxA and pslA as 100%, 80%, 40%, and 40%, respectively. S. aureus SEs genes were examined in S. aureus strains, where SEA and SEB genes were detected with 60%, but no isolate harbor SEC or SED or SEE. The significant fold change of P. aeruginosa pslA expression was 0.40332 after treatment with Moringa oleifera aqueous extract. Conclusion: P. aeruginosa and S. aureus harbor dangerous virulence genes that cause food poisoning, but Moringa oleifera extract could minimize their action. [Open Vet J 2024; 14(1.000): 164 -175 ]